Design of a working model hovercraft - Hui Min, Chow (2012)
This thesis is the design of a small-scale working model hovercraft which providing fully hovercraft basic functions. This final year project carry out by the author to fulfillment the requirement for award the degree of Bachelor Manufacturing Engineering.This designed hovercraft which has two stages of development and included two models.The first model is for PSM 1 and the second and fully functional model is for PSM 2.Basically,the hovercraft design and fabrication process is quite similar to boat, ship, or aircraft design. In this report, I had made the entire analysis requirement, formulas for thrust and lift,drag components calculation and other important parameters to realization the design of the working model hovercraft.On the other hand,this report is aim to provided objective and scope of the research,the literature review study,research methodology,and fabrication process with result analysis and conclusion as part of requirement in submitted the report to PSM supervisor.Although hovercraft research and development is still new technology in Malaysia and no domestic consumption in this technology,but through this project it can help the industry a step further.It is because this project can categorized as successful and working as expected.Finally,I wish this project can carry on research and design development by interest manufacturing students.